SHORT MESSAGE ENCRYPTION APPLICATION DEVELOPMENT USING VIGENERE ALGORITHM UTILIZING EULER'S NUMBER ON ANDROID SMARTPHONE - Nofiyanto, Nofiyanto; Hamzah, Hamzah; Surbakti, Herison (Universitas Respati Yogyakarta, 2014)
SMS (Short Message Service) is a facility for sending and receiving a short message of text by using a cell phone. SMS is a medium of communication that is easy to use and relatively cheap for SMS costs. Messages sent via SMS does not guarantee the security and confidential because messages that are sent using the default SMS application for your mobile phone is still an open text that has not been protected. Therefore, it takes a method and applications to secure the confidentiality of the information in an SMS message.This research aims to develop short message encryption applications on android smartphones using Vigenere algorithm utilizing euler's number as a safety and maintaining the confidentiality of this SMS only to a functioning android smartphone users to send messages and message encryption as well as receive incoming messages and decrypt the message. Starting from the early stages of identifying, needs analysis, design, implementation and testing.Application of message encryption using vigenere algorithm utilizing euler's number digit can help users of android smartphone to secure the contents of the message are confidential.Â Â Keywords: Short Message Service, the number of euler, vigenere algorithm